Identifikasi Arsitektur Fasade Art Deco Dikaitkan Dengan Fungsi Bangunan Museum - Dwipa, Novantio; R. Sukardi, Rahy; Astrid Hartoety, Dianna (Jurnal Syntax Fusion, 2024)
Indonesia has many architectural styles, the biggest cause of architectural development in Indonesia was the colonial events carried out by Europeans and Japanese. The city of Bandung is called "Art Deco City" because there are historical buildings that have an art deco architectural style which is a legacy of the Dutch colonial era. This research aims to reveal the facade of the geology museum building and determine the relationship between the building facade and the function of the museum building. This research is aimed at buildings that are more than fifty years old and whose physical condition has relatively not changed significantly. This research uses a qualitative descriptive research method. The results of the research show that the geology museum building is a building with art deco architecture combined with West Javanese vernacular architecture. The facade of the geology museum building supports the museum's function as a place to store and protect research and study items. However, in the context of exhibitions and communications, there are deficiencies in doors as circulation and windows as lighting support.